تعليم الخط العربي في معهد المصدوقية الإسلامي: مشكلاته وحلوله - Ahmad Kamil Fadoli; Ahmad Yasir Amrulloh (Universitas Negeri Malang, 2022)
Teaching calligraphy is one of the most important things, but it is not without problems during education, and so is the case of teaching calligraphy at the Islamic Institute of Validity. The research aims to describe the process of teaching calligraphy at the Islamic Institute of Validity In terms of its problems and solutions. The descriptive qualitative approach was used. Data collection by observation, interview, and documentation. And their analysis by the three method of Mills and Huberman is data reduction, presentation and inference. And its sources from the teacher of improving Arabic calligraphy and his students. The results indicated that learning the calligraphy takes place in the way of the extensive vocabulary and structures in the Naskhi script and its models from the Qur’anic verses and the honorable hadiths. His problems depend on the internal and external problem, which is that the teacher was not accurate in correction, did not teach the students to generate letters and their analogies, did not order the students to write the job at the beginning of the study, and the students’ lack of desire to teach calligraphy. As for its solutions, the teacher corrects the students accurately by applying a number of calligraphy theories, teaches them to generate letters and their analogies, instructs them to write calligraphy before teaching, and defends them about the importance of teaching Arabic calligraphy.